Polypyrrole/nanocellulose composite for food preservation: Barrier and antioxidant characterization. (June 2017) - Bideau, Benoit; Bras, Julien; Adoui, Nawel; Loranger, Eric; Daneault, Claude
Graphical abstract: Highlights: The TOCN/PVA-PPy composite is really interesting for food packaging application. Polypyrrole confers high barrier properties against oxygen and water vapor diffusion. Polypyrrole gives good antioxidant character to the composite. The composite is highly biodegradable. Abstract: When food cannot be consumed immediately after production, food packaging must create a protective atmosphere around the food product. The packaging must improve the shelf life of perishable foods and protect the food from dirt, dust, oxygen, light, pathogenic microorganisms, and moisture by acting as an effective barrier to moisture, gases (CO2 and O2 ) or even by possessing antimicrobial properties. However, extending the shelf life and enhancing food quality while reducing packaging waste is encouraged. The exploration of new bio-based packaging materials, such as TEMPO-oxidize nanofibrillated cellulose (TOCN), has increased due to its biodegradable and renewable character. This work emphasizes the antioxidant activity and high barrier properties against the diffusion of oxygen, carbon dioxide and water vapor from a nanocomposite based on polypyrrole (PPy) and TOCN, as well as its biodegradability for food packaging applications. The preparation, characterization and application of the nanocomposite in food packaging are discussed.